2020
DOI: 10.3390/cells9122710
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Regulatory Interactions between NF-κB and the Pluripotency Factor Lin28

Abstract: An appreciation for the complex interactions between the NF-κB transcription factor and the Lin28 RNA binding protein/let-7 microRNA pathways has grown substantially over the past decade. Both the NF-κB and Lin28/let-7 pathways are master regulators impacting cell survival, growth and proliferation, and an understanding of how interfaces between these pathways participate in governing pluripotency, progenitor differentiation, and neuroplastic responses remains an emerging area of research. In this review, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 126 publications
(177 reference statements)
0
4
0
Order By: Relevance
“…This result correlated with reduced CXCL8 and COX-2 mRNA and protein levels, whereas the secretion of IL-6 (a biomarker, among others, of arthralgia/arthritis persistence and severity following alphaviral infection [28,46]) appeared to be modulated at the post-transcriptional level. In this sense, post-transcriptional-level interactions between NF-κB and the Lin28/let-7 pathway were recently described in the review written by Mills IV et al and showed that NF-κB mediates Lin28b expression, an inhibitor of Let-7 miRNA family members, themselves known to reduce IL-6 production by interfering with the 3 UTR region of its mRNA [47]. This review also evidences many predicted interactions between let-7 miRNA and mRNA related to NF-κB subunits, including, among others, interactions that repress p105 mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…This result correlated with reduced CXCL8 and COX-2 mRNA and protein levels, whereas the secretion of IL-6 (a biomarker, among others, of arthralgia/arthritis persistence and severity following alphaviral infection [28,46]) appeared to be modulated at the post-transcriptional level. In this sense, post-transcriptional-level interactions between NF-κB and the Lin28/let-7 pathway were recently described in the review written by Mills IV et al and showed that NF-κB mediates Lin28b expression, an inhibitor of Let-7 miRNA family members, themselves known to reduce IL-6 production by interfering with the 3 UTR region of its mRNA [47]. This review also evidences many predicted interactions between let-7 miRNA and mRNA related to NF-κB subunits, including, among others, interactions that repress p105 mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, although the WNT pathway plays a central role in regulating proliferation during development and in stem cell self-renewal, WNT reactivation did not affect cell proliferation or cell cycle markers, indicating that HypOsm-mediated WNT inhibition is necessary to promote transcriptional maturation but not growth arrest. NF-kB activity levels have been reported to increase during differentiation 93 and mouse and human PSC missing key NF-κВ components cannot differentiate 94,95 , emphasizing the importance of the NF-κВ pathway in mediating cellular differentiation. As NFAT5, induced under hyperosmolar conditions is a cofactor of the NF-κВ signaling cascade 96 , the inhibition of IKK2 suppresses the osmo-protective response as NFAT5 is unable to drive its target expression.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB activity levels have been reported to increase during neuronal and vascular differentiation [66,98] and mouse and human PSC missing key NF-𝜅В components cannot differentiate, [66,99] emphasizing the importance of the NF-𝜅В pathway in mediating cellular differentiation. As NFAT5, induced under hyperosmolar conditions is a co-factor of the NF-𝜅В signaling cascade, [100] the inhibition of IKK2 suppresses the osmo-protective response as NFAT5 is unable to drive its target expression.…”
Section: Discussionmentioning
confidence: 99%